2006
DOI: 10.1097/01.sla.0000201452.09591.f3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Carbonic Anhydrase IX (CA IX), a Hypoxia-Related Protein, Rather Than Vascular-Endothelial Growth Factor (VEGF), a Pro-Angiogenic Factor, Correlates With an Extremely Poor Prognosis in Esophageal and Gastric Adenocarcinomas

Abstract: The difference in expression of CA IX and VEGF between intestinal- and diffuse-type adenocarcinomas may possibly explain the different clinical behavior of these tumors. CA IX expression, rather than VEGF positivity in tumors, enables the identification of a subpopulation, characterized by a more aggressive behavior and a poorer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
103
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 41 publications
7
103
0
3
Order By: Relevance
“…Further studies are therefore necessary to clarify the mechanisms responsible for survival in an environment with a partial oxygen tension o10 mm Hg. It has been reported that tumour hypoxia is associated with more aggressive tumour phenotypes, which may lead to a poorer prognosis for patients (Imai et al, 2003;Driessen et al, 2006;Mayer et al, 2008). Our hypoxia models using OCUM-12/Hypo cells showed frequent lymph node metastasis.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Further studies are therefore necessary to clarify the mechanisms responsible for survival in an environment with a partial oxygen tension o10 mm Hg. It has been reported that tumour hypoxia is associated with more aggressive tumour phenotypes, which may lead to a poorer prognosis for patients (Imai et al, 2003;Driessen et al, 2006;Mayer et al, 2008). Our hypoxia models using OCUM-12/Hypo cells showed frequent lymph node metastasis.…”
Section: Discussionmentioning
confidence: 80%
“…Cancer cells under hypoxic conditions are reported to show malignant features, such as high metastatic ability and resistance to various anti-cancer therapies (Harris and Shrieve, 1979;Ludwig, 1984;Driessen et al, 2006); however, the mechanisms by which hypoxia affects cancer progression remain unclear. Hypoxia alters important intracellular pathways, and it is recognized as a stimulus for the malignant potential (Semenza, 2002;Subarsky and Hill, 2003;Vaupel, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NSCLC and gastric cancer are 2 of several tumor indications showing CAIX expression as well as sensitivity to taxanes (29)(30)(31). The expression of CAIX varies between tumor indications as well as between individual patients with a tumor of the same histologic origin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CA9 expression is an independent prognostic marker in oesophageal and gastric adenocarcinomas (Driessen et al, 2006), but the relationship between prognosis and CA9 expression in oesophageal squamous cell carcinoma (ESCC) remains controversial.…”
mentioning
confidence: 99%